The impact of institutions, law and corruption in business environment - Evidence for Kosovo - Zogjani, Jeton; Mazelliu, Majlinda; Humolli, Baton; Qehaja, Vesa; Kunushevci, Artan (Advances in Social Sciences Research Journal, 2017)
Business environment across different time periods of transition is challenged from different implications, such as: political and institutional instability, inadequate laws and corruption steadily and continuously increasing in transition countries. The main overview of research paper is focused in process of reforms and priority in business environment in transition countries. Then is identify the main obstacles and difficulties that business environment is faced in Kosovo and in detail is presented the reforms that are made from Kosovo institutions in business environment over the past few years. Through OLS method are analyzed separately three main areas that are included in research paper (institutions, law and corruption in business environment). The results have shown that institutions (through business policies) have positive impact on business environment, but political stability in Kosovo has negative impact in business environment. In analysis between law and business environment is appeared that role of law has negative impact in business environment, but protecting investors (through law) has shown positive impact in business environment. In the third analysis of corruption both variables (corruption and bribery) have shown positive impact in business environment in Kosovo. Kosovo should establish sustainable institutions, enforce the law and to reduce drastically the corruption, these are the main priority for a stable business environment. Furthermore, Kosovo should continue to improve the process of reforms in order to create a favorable business environment (such is in developed countries). Keywords: bribery costs, business climate, regression method, political stability, protecting investors